PENGARUH MULTIMEDIA PEMBELAJARAN MATEMATIKA BERBASIS GOOGLE SITES TERHADAP MOTIVASI BELAJAR - Prayoga, Ananda; Yusmin, Edy; Munaldus, Munaldus; Jamiah, Yulis; Siregar, Nurfadilah (UNIVERSITAS TANJUNGPURA, 2023)
In this study, researchers used Pre-Experimental Design with the form of One Group Pretest-Posttest Design. the sample in this study were 32 students of class XI TITL at SMK Negeri 2 Pontianak. the data collection technique in this study was an indirect communication technique using a questionnaire. The learning motivation of students who do not use multimedia martematics learning based on google sites has an average percentage of 71% (high). The learning motivation of students who use multimedia learning martematics based on google sites has an average percentage of 82% (very high). The effect of using multimedia learning martematics based on google sites on the learning motivation of class XI students at SMK Negeri 2 Pontianak is evidenced by the results of the Wilcoxon test whose probability value or Sig. 2 tailed of 0.000 <0.05 and an effect size value of 1.021 which shows an increase in learning motivation in the large category. Thus it can be concluded that the use of multimedia learning martematics based on google sites has a major effect on student learning motivation.